2016
DOI: 10.5336/nurses.2013-38415
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Nurses Tracheostomy/Endotracheal Tube Cuff Pressure Practices in Intensive Care Units

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: Bu çalışma, hemşirelerin endotrakeal tüp (ETT)/trakeostomi tüpü (TT) kaf basıncı uygulamaları konusundaki bilgi ve uygulamalarını belirlemek amacıyla tanımlayıcı olarak yapılmıştır. G Ge er re eç ç--Y Yö ön nt te em m: Çalışmaya yoğun bakım ünitelerinde en az altı ay çalışan hemşireler dahil edilmiştir. Araştırmaya katılmayı kabul eden ve araştırmanın amacına uygun olarak ETT/TT kaf basıncı uygulamalarının yapıldığı altı farklı yoğun bakım ünitesinde çalışan 120 hemşireden 80'i çalış… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Also this study determined that nurses need information about endotracheal or tracheostomy tube cuff pressure practices [18]. Similarly in our study, it was concluded that nurses working in our intensive care unit had lack of knowledge and lack of training about cuff pressure monitoring and cuff exercises, despite they have education degree.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Also this study determined that nurses need information about endotracheal or tracheostomy tube cuff pressure practices [18]. Similarly in our study, it was concluded that nurses working in our intensive care unit had lack of knowledge and lack of training about cuff pressure monitoring and cuff exercises, despite they have education degree.…”
Section: Discussionsupporting
confidence: 58%
“…A study indicate 20% of the nurses stated that they measure that he speaks appropriately once a shift, while more than half of them 52% state that they measure when the mechanical ventilator gives an alarm [18]. In our study %78,6 of participant nurses frequency of measure cuff pressure less then necessary.…”
Section: Discussionmentioning
confidence: 53%